A Study on Multiple Load Conditions Analysis for a Bicycle Chassis - Choo, Wou Onn; Muhammad Izzat Nor, Ma'arof; Wong, Winson, Zu Xian; Lim, Khai Hen; Girma, Tadesse Chala (INTI International University, 2022)
In Malaysia, mass utilization of bicycle as a “green approach” in ensuring environmental sustainability and minimizing over reliant on fossil fuel is indeed a great idea. One of the prominent components of a bicycle is its chassis. Chassis is the main part of a bicycle, where it absorbs all the load acting on it. The chassis plays important role in of safety as well as comfort. The aim of this study was to investigate on the multiple loading conditions on a bicycle chassis. For this study, an existing bicycle chassis design that was available in the market was selected to investigate. The specification details of the chassis were obtained from the manufacturer’s website and then developed via the use of Computer Aided Design (CAD). The chassis was then analyzed via Finite Element Analysis (FEA) software for the following loading conditions: (i) Static start-up (ii) Steady pedaling (iii) Vertical loading (iv) Horizontal loading and (v) Rear wheel braking. The result of the analysis was shown the reading and position of maximum equivalent (von Mises) stress of the frame, reading of safety factor and weight for each design in normal and expandable mode under each load conditions. The highest of maximum stresses were found in the load condition 3 which was the vertical loading. The lowest maximum stress of the designs was found in the load conditions 4 which was rear wheel braking. The safety factors for certain loading condition were greater than 2.0. Hence, further design optimization could be made with this aspect. As a conclusion, the assessments were a success. The data attained from this assessment could now be utilized as a benchmark for future improvements on overall chassis design, engineering material or human factors.